2016
DOI: 10.1371/journal.pone.0157100
|View full text |Cite
|
Sign up to set email alerts
|

FLCN Maintains the Leucine Level in Lysosome to Stimulate mTORC1

Abstract: The intracellular amino acid pool within lysosome is a signal that stimulates the nutrient-sensing mTORC1 signalling pathway. The signal transduction cascade has garnered much attention, but little is known about the sequestration of the signalling molecules within the lysosome. Using human HEK293 cells as a model, we found that suppression of the BHD syndrome gene FLCN reduced the leucine level in lysosome, which correlated with decreased mTORC1 activity. Both consequences could be reversed by supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 49 publications
5
46
0
Order By: Relevance
“…C, lower panel). This result has been attributed to the reduced amino acids pool in the lysosome, which was caused by the excessive lysosome‐anchored PAT1 . Surprisingly, we found that mTORC1 activities were either unchanged or modestly increased in three different cell lines stably expressing the EGFP‐PAT1 3NQ (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…C, lower panel). This result has been attributed to the reduced amino acids pool in the lysosome, which was caused by the excessive lysosome‐anchored PAT1 . Surprisingly, we found that mTORC1 activities were either unchanged or modestly increased in three different cell lines stably expressing the EGFP‐PAT1 3NQ (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…In a previous study , we generated stable 293 cell lines expressing EGFP‐PAT1, which encodes a human PAT1 fusion protein with an N‐terminal EGFP tag. Using these cells as a model, we found that some EGFP‐PAT1 proteins were present on the lysosome and that overexpression of EGFP‐PAT1 decreased mTORC1 activity . Similar results have been reported by other studies through checking either the endogenous PAT1 (for the localization assay) or chimeric PAT1 fused with different tags .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FLCN is recruited to the lysosome by interaction with RagA/B GDP and requires GATOR1 GAP activity; FLCN recruitment to the lysosome is thus likely regulated by the same set of amino acid sensors upstream of GATOR1/2 that act to regulate mTORC1 68 . One possible explanation for the localization of FLCN to the lysosome following amino acid depletion was recently discovered: FLCN sequesters lysosomal leucine when amino acids are limited by blocking PAT1, a lysosomal amino acid transporter, thus helping to preserve mTORC1 activity during nutrient limitation 69 .…”
Section: Regulators Of the Rag Gtpasesmentioning
confidence: 99%